A case study on feedback on EAP writing in a HEI in OMAN - AL Harrasi, Kothar Talib Sulaiman (2019)
This research explored how feedback on English for Academic Purposes (EAP) writing was interpreted, enacted and developed by students, teachers and college leaders in a higher education institution (HEI) in Oman. The focus of the study was on probing the views and discursive practices of students and teachers, and on the college policy and guidance in relation to feedback on academic writing. The research posed a question that had largely been examined in previous research, such as Carless’ (2006) study which explored the different perceptions of teachers and students towards the feedback process, assessment and marking in an L2 writing context. However, previous studies had not captured the underlying complexities, or the different levels of context surrounding the feedback practices, such as the influence of EAP writing on feedback practices. Therefore, this study investigated feedback on EAP writing in a particular HEI in Oman, where it explored feedback in a natural setting, putting emphasis on the social practices of teachers, students and college leaders. This study interviewed participants to find out their beliefs about feedback and EAP writing, as well as scrutinising the college stated policy about feedback. The study also examined actual feedback practices through observation, analysis of student writing and analysis of college documents. The findings of this study showed that feedback practices in the Omani institution did not occur in isolation but were always surrounded by contextual influences. The analysis revealed that the practices of feedback were influenced by three levels of context: the local, the EAP writing and the institutional. First, feedback practices were found to be shaped by classroom interactions that occurred between teacher and students, or among students themselves, which were constructed by their beliefs about feedback and EAP writing, student self-directed learning, and teacher practices in giving feedback. Additionally, it was found that feedback practices were constructed in line with EAP writing pedagogy and academic conventions; e.g. student response to feedback was determined by their understanding of EAP academic conventions. Finally, feedback was found to be influenced by the institutional context which concerned college support for feedback, including coaching, to help use and interpret policies and feedback. Practical and theoretical implications are offered to researchers, teachers, students and college leaders based on the findings of the study. For example, based on the overall investigation of contextual influences in the institution, it is recommended to encourage teachers and students in their feedback practices, minimise any structural constraints that impede their practices, communicate college instructions clearly, build the competence of teachers and students, and provide transparent results for teacher and student efforts in enhancing their feedback practices.